Development of Factors and Indicators of Learning Leadership of Secondary School Heads of Departments under the Office of Secondary Educational Service Area, Bangkok - Wanprakob, Somporn; Kajonsilp, Boonriang; Prasertsin, Ujsara (Rajapark Journal, 2022)
The research objectives were to 1) develop the factors and indicators of learning leadership 2) verify the suitability and practical of possibility in the factors and indicators of learning leadership 3) verify the construct validity and determine the level of learning leadership. The research design was mixed-method research. The samples were: group 1 - step 1 consisted of 5 leadership experts; group 2 – step 2.1 consisted of 7 educational administration experts, step 2.2 consisted of 280 school department heads, and group 3 consisted of 417 school department heads. The research instruments used were interview forms, questionnaire note forms in the focus group discussions, the questionnaire about the practical possibility, and the evaluation form of secondary school department heads. Data analysis was with content analysis and practical suitability, verifying the construct validity and determining the levels of learning leadership. The results of the research were as follows: 1) Learning leadership of school department heads consisted of 6 factors and 22 indicators, namely: (1) Shared Team Learning (5 indicators), (2) Educational Environment Management (3 indicators), (3) Innovation and Technology Learning (3 indicators), (4) Higher Order Thinking (4 indicators), (5) Self-learning (3 indicators), and (6) Integration for Instructional Development (4 indicators). 2) All factors and indicators were suitable and tended to be practical with more than 80 percent of respondents and 3) The study has found that factors and indicators had construct validity and the learning leadership of secondary school heads of departments was at a high level.